*This preview shows
pages
1–7. Sign up
to
view the full content.*

This
** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*This
** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*This
** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*
**Unformatted text preview: **-=-+ + = Multiply (1) by -1 (1) (2)--+ =-+ + = 2 6 12 2 3 4 4 2 2 2 2 x y y x y y Add (1) and (2)- + + = 9 16 4 2 y y Use the elimination method when both x and y are squared in each equation. ( 29 ( 29- + + = - - - = 9 16 4 9 2 2 2 y y y y y y = -= 2 9 2 or For y = -2/9: 12 6 2 2 2 =-+ y y x 2 6 2 9 12 2 9 2 2 x +- -- = 2 80 27 2 x + = No Solution For y = 2: 12 6 2 2 2 =-+ y y x 2 6 2 12 2 2 2 x + - = ( ) ( ) 2 24 24 2 x +-= 2 0 2 x = x = 0 Solution: (0, 2)...

View
Full
Document